Bacteriological Assessment of Different Root Canal Irrigants - Hussain F Al-Huwaizi
Aim of the study: To evaluate the antibacterial action of different root canal irrigants. Materials and method: By the use of the zone of inhibition method, sodium hypochlorite (2.5% and 5%), acetic acid (2%), sodium chloride solutions (5 and 10%), and normal saline, were assessed bacteriologically against inhabitants of necrotic root canals. Results: Sodium hypochlorite solutions and 2% acetic acid showed efficient antibacterial action. Five percent sodium hypochlorite gained the most superior results, followed by 2% acetic acid, then 2.5% sodium hypochlorite. The sodium chloride solutions showed no antibacterial action. Conclusion: Sodium hypochlorite (2.5% and 5%), and 2% acetic acid have efficient antibacterial action against the necrotic root canal bacteria.